2003
DOI: 10.1103/physreve.67.031405
|View full text |Cite
|
Sign up to set email alerts
|

Aging processes and scale dependence in soft glassy colloidal suspensions

Abstract: The aging behavior of colloidal suspensions of laponite, a model synthetic clay, is investigated using light scattering techniques. In order to measure the complete dynamic structure factor as a function of time and of wave vector, we have developed an original optical setup using a multispeckle technique for simple light scattering. We have thus measured the correlation of the scattered light intensity as a function of the age of the sample t(w) for various concentrations. For sufficiently concentrated sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
194
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(221 citation statements)
references
References 29 publications
22
194
3
Order By: Relevance
“…The full lines show the glassy and dotted lines show the gel line, obtained by averaging over all the samples measured. [6,10] have been invoked and were thought to be mutually exclusive [6,9]. We here provided clear experimental evidence for how the distinction of gel and glassy states can be made [16].…”
Section: Fig 4 (A)mentioning
confidence: 90%
See 1 more Smart Citation
“…The full lines show the glassy and dotted lines show the gel line, obtained by averaging over all the samples measured. [6,10] have been invoked and were thought to be mutually exclusive [6,9]. We here provided clear experimental evidence for how the distinction of gel and glassy states can be made [16].…”
Section: Fig 4 (A)mentioning
confidence: 90%
“…The system we consider is a suspension of anisotropic and charged colloidal particles suspended in water: Laponite, a synthetic clay [5][6][7][8][9][10]. The study of colloids allowed for a significant contribution to elucidating the basic physics of glass transition [11,12].…”
Section: Gels and Glasses In A Single System: Evidence For An Intricamentioning
confidence: 99%
“…This equation is not derived from any first principle argument, rather it embodies the exponential growth of the τ m for short t w (as previously observed [6,19,24]) and the existence of a divergence of τ m at a finite value of t w , i.e. t ∞ w .…”
Section: B the Slow Dynamics: The B Parameter And The Aggregation Ratementioning
confidence: 99%
“…The most studied part of the phase diagram is the one at low salt concentration (usually samples are prepared in pure deionized water, C s ≃ 1 × 10 −4 M) and intermediate clay concentration (C w ≃ 3%). In this region several dynamical light scattering measurements have shown that the samples initially liquids age towards an arrested phase [2,3,4,5,6] but the mechanism of aggregation is not clear. The gel/glass state has been in fact attributed by different authors to Wigner glass transition [3], frustrated nematic transition [1,7,8,9], micro-segregation [1,10,11], gelation [12,13,14], etc..…”
Section: Introductionmentioning
confidence: 99%
“…(d) G (ω) (squares) and G (ω) (circles), acquired from a 5 wt.% montmorillonite clay (Bentonite) suspension [152], display the features predicted in [153]. relaxation τ ∼ t µ w , with µ ≈1 [156]. For smaller waiting times, hyper-aging dynamics (µ > 1) has been observed [157].…”
Section: Soft Glassy Rheologymentioning
confidence: 99%